Influence of Information Asymmetry and Self-Efficacy on Budgetary Slack: An Experimental Study - Zaenal Fanani; Georgina Elizabeth K. Saudale (Jurnal Akuntansi dan Keuangan, 2019)
Participation in the budgetary process does not only comes with a positive effect(s) but could also lead to negative behavior(s) of employees, one of which is the creation of budgetary slack. Previous studies said that information asymmetry is rated as one of the causes of the creation of budgetary slack. The purposes of this 3x2 factorial experimental study and between subject designs are to see the effect of information asymmetry on the budgetary slack and see whether information asymmetry and self-efficacy leads to the creation of budgetary slack. This study involved 65 undergraduate and postgraduate students from the accounting department of Economics and Business Faculty in Universitas Airlangga Surabaya as participants. One way ANOVA and two- way ANOVA is used to test and analyze the proposed hypothesis. Results show that information asymmetry influences the creation of budgetary slack. However, production managers with high or low self-efficacy are still taking advantage of asymmetric information that happened to do budgetary slack.